Hubungan antara Persepsi Siswa dengan Minat Siswa Mengikuti Layanan BK Format Klasikal - Primaheni, Firda; Suharso, Suharso (Indonesian Journal of Guidance and Counseling: Theory and Application, 2015)
Minat siswa dalam mengikuti layanan BK format klasikal dipengaruhi oleh faktor internal dan eksternal. Faktor internal diantaranya adalah persepsi siswa tentang proses pelaksanaan layanan BK format klasikal. Penelitian ini bertujuan untuk menganalisis hubungan antara persepsi siswa tentang proses pelaksanaan layanan BK format klasikal dengan minat siswa dalam mengikuti layanan BK format klasikal. Penelitian ini merupakan penelitian korelasional. Subjek dalam penelitian ini adalah 96 siswa kelas X IPA dan IPS di SMA N 5 Semarang. Data diambil dengan instrumen berupa skala persepsi dan skala minat. Hasil dari uji korelasi menunjukkan bahwa ada hubungan antara antara persepsi siswa tentang proses pelaksanaan layanan BK format klasikal dengan minat siswa dalam mengikuti layanan BK format klasikal yang ditunjukkan dengan koefisien korelasi (r) sebesar 0,348 dengan taraf signifikansi 5%, maka rh> rt. Dari hasil ini dapat disimpulkan bahwa ada hubungan positif namun korelasi tidak cukup kuat antara persepsi siswa tentang proses pelaksanaan layanan BK format klasikal dengan minat siswa dalam mengikuti layanan BK format klasikal. The student interest in participating in a BK’s classical format services is influenced by internal and external factors. Internal factors include the perceptions of students about the process of implementing the service of BK’s classical format. This study aimed to analyze the relationship between students 'perception of the service implementation process of BK’s classical format with students' interest in participating a BK’s services classical format. This research is correlational. Subjects in this study were 96 students of class X science and social studies in high school N 5 Semarang. Data taken with instruments such as the perception of scale and the scale of interest. Results of correlation test showed that there is a relationship between the perceptions of students about the process of implementing the service of BK’s classical formats with the students' interest in participating in the service of BK’s classical format demonstrated by the correlation coefficient (r) of 0.348 with a significance level of 5%, then rh> rt. From these results it can be concluded that there is a positive correlation but not a strong enough correlation between students 'perception of the service implementation process of BK’s classical format with students' interest in participating BK’s classical format service.